2016
DOI: 10.1007/s00192-015-2918-z
|View full text |Cite
|
Sign up to set email alerts
|

Is prenatal urethral descent a risk factor for urinary incontinence during pregnancy and the postpartum period?

Abstract: Prenatal urethral descent and UI during pregnancy are risk factors for UI at 1 year postpartum. These results indicate that postnatal UI is more strongly influenced by susceptibility factors existing before first delivery than by the mode of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
3
10
0
3
Order By: Relevance
“…A recent study found that BND during pregnancy correlated to UI after delivery. 24 We found a similar correlation for RVA to SUI, but as in the study by Pizzoferrato et al, UI symptoms during pregnancy were a stronger predictor for UI after delivery. Attempts have been made to establish a cut off for normality for BND.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A recent study found that BND during pregnancy correlated to UI after delivery. 24 We found a similar correlation for RVA to SUI, but as in the study by Pizzoferrato et al, UI symptoms during pregnancy were a stronger predictor for UI after delivery. Attempts have been made to establish a cut off for normality for BND.…”
Section: Discussionsupporting
confidence: 88%
“…If ultrasound measurements during pregnancy could be used to predict which women would be at higher risk to develop UI after delivery, it could help identify women who would potentially benefit from pelvic floor muscle exercise during pregnancy and after delivery. A recent study found that BND during pregnancy correlated to UI after delivery . We found a similar correlation for RVA to SUI, but as in the study by Pizzoferrato et al, UI symptoms during pregnancy were a stronger predictor for UI after delivery.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Cela permettra, j'espè re, d'é branler les fausses croyances encore largement communes à propos du caractè re traumatique de l'accouchement vaginal. Il faut encore rappeler que l'incontinence urinaire est particuliè rement fré quente pendant la grossesse (entre 30 et 50 % des femmes rapportent des fuites urinaires pendant la premiè re grossesse) [4], et aussi qu'il est possible de pré dire le risque d'incontinence urinaire postnatale en observant la mobilité uré trale avant l'accouchement [5]. Une grande partie de ce qui dé termine l'incontinence urinaire de la femme est donc probablement à rechercher ailleurs que dans le mode d'accouchement et dè s la pé riode pré natale.…”
Section: Outbreak Of Caesarean Sections and Fear Of Birth Injuryunclassified